2018
DOI: 10.14419/ijet.v7i2.5.13951
|View full text |Cite
|
Sign up to set email alerts
|

Ads Block Management System Using Open Virtual Private Network on Ubuntu Operating System

Abstract: In internet, an ad is something that able to be avoided when opening a web page. At this time many internet based businesses rely on advertising for their income. However, users are dissatisfied with the presence of ads on websites they visit, since the size of the ad data is often proportional to the actual content ads. This impacts not only on loading web pages and may lead to a file that may potentially be a carrier of the virus and may damage the operating system of the visitor. A system that can overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the clustering technique, there are several algorithms that can be applied, one of the algorithms that is quite familiar is the K-Means algorithm. In a study conducted by Syahputra, et al (2018) which used the K-Means algorithm for clustering lecturer assessments based on the Student Satisfaction Index, from the results of the study it was concluded that it was necessary to increase the clustering accuracy of the K-Means algorithm. The K-Means algorithm has several variations of development, one of the results of this development is the K-Means++ algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In the clustering technique, there are several algorithms that can be applied, one of the algorithms that is quite familiar is the K-Means algorithm. In a study conducted by Syahputra, et al (2018) which used the K-Means algorithm for clustering lecturer assessments based on the Student Satisfaction Index, from the results of the study it was concluded that it was necessary to increase the clustering accuracy of the K-Means algorithm. The K-Means algorithm has several variations of development, one of the results of this development is the K-Means++ algorithm.…”
Section: Introductionmentioning
confidence: 99%